PLASTIC ANALYSIS OF STEEL FRAME STRUCTURE - M. Rogac; M. Knezevic; M. Cvetkovska (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2012)
This paper presents the plastic analysis of steel frame structure loaded by gravity loads. By applying the cinematic theorem of ultimate analysis, the ultimate load for the case of elastic - ideally plastic material is calculated. The identical structure was treated in the computer program SAP2000 where the zone of material reinforcement in the plastic area was covered. Keywords: Steel frame structure, plastic analysis, ultimate gravity load, material reinforcement.